2017
DOI: 10.1186/s12977-017-0349-2
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon signaling is required for the APOBEC3/Rfv3-dependent neutralizing antibody response but not innate retrovirus restriction

Abstract: BackgroundAPOBEC3/Rfv3 restricts acute Friend retrovirus (FV) infection and promotes virus-specific neutralizing antibody (NAb) responses. Classical Rfv3 studies utilized FV stocks containing lactate-dehydrogenase elevating virus (LDV), a potent type I interferon inducer. Previously, we showed that APOBEC3 is required for the anti-FV activity of exogenous IFN-alpha treatment. Thus, type I interferon receptor (IFNAR) signaling may be required for the APOBEC3/Rfv3 response.ResultsTo test if the APOBEC3/Rfv3 resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…These observations suggest that IFN-α plays a role in enhancing and regulating antibody affinity, and they correlate with studies that highlighted the important role of mTORC1 in the antibody response 17,18,54 . In addition, studies have shown that IFN-α enhances B-cell class switching 24 , and promotes a neutralizing antibody response against virus infection 55 . Reduced IFN-α expression via decreased mTORC1 signalling in individuals with T2DM who were prescribed metformin may lead to reduced selection of germinal centres and affinity maturation.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that IFN-α plays a role in enhancing and regulating antibody affinity, and they correlate with studies that highlighted the important role of mTORC1 in the antibody response 17,18,54 . In addition, studies have shown that IFN-α enhances B-cell class switching 24 , and promotes a neutralizing antibody response against virus infection 55 . Reduced IFN-α expression via decreased mTORC1 signalling in individuals with T2DM who were prescribed metformin may lead to reduced selection of germinal centres and affinity maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Type I interferons induce the expression of interferon-stimulated genes, including STAT1/2, SOCS and A3s. IFNα induces A3s through the type I IFN receptor and activation of PKC and STAT1, and inhibition of PKC prevents the induction of A3B in breast cells ( 37–42 , 48 , 49 ). IFNα treatment is used in treating chronic hepatitis B and recent cell culture studies have shown that induction of A3 and BER by IFNα treatment is essential for decreasing hepatitis B virus ( 39 , 50–52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mA3 acted as the major effector molecule of exogenously-administered IFNα therapy. Interestingly, in an IFNAR KO background, mA3 still reduced early infectious viremia, though not via antibody-mediated mechanisms (Barrett et al 2017). Furthermore, this reduction of infectious viremia occurred in the presence or absence of LDV.…”
Section: Apobec3mentioning
confidence: 99%
“…This is not surprising, since murine retroviruses seem to suppress endogenous IFN I production, minimizing IFN signaling during acute infection (Lin et al 2014). However, in an mA3 deficient background, the loss of IFNAR increased acute FV viremia (Barrett et al 2017). These findings suggest that the low amount of virus-induced type I IFN triggered antiviral effectors other than mA3 that contributed to inhibiting acute FV replication in vivo.…”
Section: Apobec3mentioning
confidence: 99%
See 1 more Smart Citation